POLA KEPEMIMPINAN KH. ARIFIN ILHAM DALAM PENGEMBANGAN YAYASAN AZ-ZIKRA SENTUL KABUPATEN BOGOR - Mubarraq, Alwahyu (ALAMIAH : Jurnal Muamalah dan Ekonomi Syariah, 2024)
Leadership in the Az-Zikra Islamic boarding school is an effort to educate students who are led in this case by a pesantren leader to teachers, students and staff to carry out pesantren activities that have been discussed with the aim of carrying out effectively as taught by the great prophet Muhammad SAW. The problem that researchers encountered was that the previous leadership at the Azzikra Islamic Boarding School was due to a leadership figure, KH. Muhammad Arifin Ilham so that after his death no one could be like the figure of murabbi KH. Muhammad Arifin Ilham therefore the importance of a leadership system in the Az-Zikra Islamic boarding school so that whoever leads it continues as usual because the pesantren system that has been planned is in accordance with the ideals of KH. Muhammad Arifin Ilham. "Broken grows lost changed "Before it was broken, it had grown before it was lost, there was a replacement". So the system intended to carry out teaching and learning activities at the Az-Zikra Islamic boarding school is realized from 3 important parts, namely the TMI Teaching section (Tarbiyah Mualimin Al Islamiyah), the student caregiver assistant section and the tahfidz section. The research method used in this thesis is qualitative research using a descriptive approach. The research subjects were one pesantren leader, the first wife of KH Muhammad Arifin Ilham, one ustad, two students. Data collection techniques using observation, interviews and documentation. The results of this study indicate that by implementing a leadership strategy in implementing this order, so that the Az-Zikra Islamic Boarding School can give birth to generations of robbani, millennial ulema according to the hopes and ideals of KH. Muhammad Arifin Ilham.